Global Value Chain of Indonesian Pulp and Paper Industry - Tauhid Ahmad; Arief Daryanto; Rina Oktaviani; D.S. Priyarsono (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Global Value Chain (GVC) has been a global phenomenon since 1980s when export values no longer represented the actual benefit of a country’ economic measure. Furthermore, GVC measurement applying input-output table approach has quite rapidly developed. Given the fact that the role of Indonesian pulp and paper industry is increasingly important in the country’s economy, this study aimed at measuring the pulp and paper industry GVC in 1995 and 2011 as well as its position and participation in the global GVC using Inter-Country Input-Output (ICIO). The results show that GVC of Indonesia's pulp and paper industry is generally in the form of value-added exports in intermediate absorption by direct importers and indirect final exports and also in the form of foreign value-added return in foreign countries in intermediate exports and also value-added exports in intermediate goods exports to the third countries. GVC Indonesia is also still dominated by domestic value-added compared to foreign value-added and remains in a “downstream” position and has decreased its GVC participation globally. In the future, it is important to strengthen GVC participation by maintaining greater ownership of domestic value- added in Indonesia's pulp and paper industry.Keywords: global value chain, pulp and paper, Intercountry input-output, GVC position and participation